PENGGUNAAN MEDIA RUMAH BELAJAR BERBASIS E-LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR PPKN SISWA KELAS XI TKJ - Aryani Lestari Putri; Lina Marlina (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2021)
ABSTRACT Education is a medium that has a major role in creating quality humans and providing various aspects of life. The development and progress of a country can be seen from how education can form quality Human Resources (HR). In this digital era, technology development is increasing rapidly. This happens because of the world of the Industrial Revolution 4.0 where technology is the fundamental thing in it. Workers in all fields in the era of the industrial revolution 4.0 are required to have digital skills, such as in the fields of development, economy and education. Various kinds of technology should be applied in preparing for classroom learning. One of the uses of technology in learning that makes this possible is the use of Information and Communication Technology (ICT). Where in reality that learning does not have difficulty in building by space and distance which is impossible if done naturally, but the expected reality can be realized through an innovation or renewal of the educational aspect through the concept of E-Learning. So that the use of existing or updated media is expected to be able to stimulate student motivation to be more interested in learning activities. This study aims to describe how the use of E-Learning-based Learning House media in increasing learning motivation for PPKn class XI TKJ students at SMK Negeri 1 Kragilan and to see what are the obstacles in using Rumah Belajar media and the efforts that can be made by teachers. in increasing student motivation. Keywords: E-Learning, Home Learning, Student Learning Motivation